Early life gut microbiome and its impact on childhood health and chronic conditions - Harold Nunez; Pamela A. Nieto; Ruben A. Mars; Maryam Ghavami; Cheryl Sew Hoy; Kimberley Sukhum (Gut Microbes)
The development of the gut microbiome is crucial to human health, particularly during the first three years of life. Given its role in immune development, disturbances in the establishment process of the gut microbiome may have long term consequences. This review summarizes evidence for these claims, highlighting compositional changes of the gut microbiome during this critical period of life as well as factors that affect gut microbiome development. Based on human and animal data, we conclude that the early-life microbiome is a determinant of long-term health, impacting physiological, metabolic, and immune processes. The early-life gut microbiome field faces challenges. Some of these challenges are technical, such as lack of standardized stool collection protocols, inconsistent DNA extraction methods, and outdated sequencing technologies. Other challenges are methodological: small sample sizes, lack of longitudinal studies, and poor control of confounding variables. To address these limitations, we advocate for more robust research methodologies to better understand the microbiome’s role in health and disease. Improved methods will lead to more reliable microbiome studies and a deeper understanding of its impact on health outcomes.